Readiness, riskiness and renewables : Country-level readiness and innovation in renewable energy under macroeconomic uncertainty - Bhuiyan, Mohammad Rakib Uddin; Dutta, Anupam; Uddin, Gazi Salah; Ahmed, Ali (Elsevier, 2025)
Readiness, riskiness, and renewables appear to form a “tripartite symbiosis” in the clean energy realm. Previous research underscores the significance of readiness as a prerequisite for a nation's advancement toward sustainable energy, urging careful navigation of uncertainties within this framework. Our research expands upon existing literature by delving into how country-level readiness influences a country's innovation in renewable energy in the face of uncertainty. Employing panel fixed effect threshold regression with four distinct models, we analyze this dynamic across 65 countries, representing both advanced and emerging economies. The results validate the presence of an uncertainty threshold effect across all model regressions, confirming a non-linear relationship among uncertainty, country-level readiness, and renewable energy innovation. Overall country-level readiness, along with its components—economic and social readiness—individually fosters renewable energy innovation under low uncertainty. However, this positive influence weakens as uncertainty exceeds the threshold. Conversely, governance readiness exerts a negative impact on renewable energy innovation under low uncertainty, with its detrimental effects becoming more significant at higher levels of uncertainty. The lagged uncertainty has a significant negative association with renewable energy innovation. Policymakers and investors should prioritize developing country level readiness to successfully manage the potential negative influence of uncertainties on renewable energy innovation.
Keywords: Innovation; Renewable energy; Readiness; Uncertainty; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|